Multidrug-Resistant Tuberculosis Not Due to Noncompliance but to Between-Patient Pharmacokinetic Variability - Srivastava, Shashikant (Oxford University Press, 2011)
(See the editorial commentary by Dartois, on pages 1827–9.) Background. It is believed that nonadherence is the proximate cause of multidrug-resistant tuberculosis (MDR-tuberculosis) emergence. The level of nonadherence associated with emergence of MDR-tuberculosis is unknown. Performance of a randomized controlled trial in which some patients are randomized to nonadherence would be unethical; therefore, other study designs should be utilized. Methods. We performed hollow fiber studies for both bactericidal and sterilizing effect, with inoculum spiked with 0.5% rifampin- and isoniazid-resistant isogenic strains in some experiments. Standard therapy was administered daily for 28–56 days, with extents of nonadherence varying between 0% and 100%. Sizes of drug-resistant populations were compared using analysis of variance. We also explored the effect of pharmacokinetic variability on MDR-tuberculosis emergence using computer-aided clinical trial simulations of 10 000 Cape Town, South Africa, tuberculosis patients. Results. Therapy failure was only encountered at extents of nonadherence ≥60%. Surprisingly, isoniazid- and rifampin-resistant populations did not achieve ≥1% proportion in any experiment and did not achieve a higher proportion with nonadherence. However, clinical trial simulations demonstrated that approximately 1% of tuberculosis patients with perfect adherence would still develop MDR-tuberculosis due to pharmacokinetic variability alone. Conclusions. These data, based on a preclinical model, demonstrate that nonadherence alone is not a sufficient condition for MDR-tuberculosis emergence.